2011
DOI: 10.3171/2011.5.peds1128
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically assisted versus open repair of sagittal craniosynostosis: the St. Louis Children's Hospital experience

Abstract: Object This study investigated the differences in effectiveness and morbidity between endoscopically assisted wide-vertex strip craniectomy with barrel-stave osteotomies and postoperative helmet therapy versus open calvarial vault reconstruction without helmet therapy for sagittal craniosynostosis. Methods Between 2003 and 2010, the authors prospectively observed 89 children less than 12 months old who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
141
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(152 citation statements)
references
References 34 publications
7
141
0
Order By: Relevance
“…In broad terms, these approaches appear to result in better morphological outcomes than open vertex strip craniectomy procedures, with cephalic indices within the normal range. 7,10,18,30,37,41 If the correction of the scaphocephalic deformity is an important determinant of the development of raised ICP, then one might expect these techniques to have a similar postoperative incidence to that we report for CR. However, we do not understand the mechanism by which intracranial hypertension arises in SC following surgery.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In broad terms, these approaches appear to result in better morphological outcomes than open vertex strip craniectomy procedures, with cephalic indices within the normal range. 7,10,18,30,37,41 If the correction of the scaphocephalic deformity is an important determinant of the development of raised ICP, then one might expect these techniques to have a similar postoperative incidence to that we report for CR. However, we do not understand the mechanism by which intracranial hypertension arises in SC following surgery.…”
Section: Discussionmentioning
confidence: 77%
“…7,10,17,18,30,37,41,48,52 The incidence of postoperative intracranial hypertension with these procedures has yet to be reported. In broad terms, these approaches appear to result in better morphological outcomes than open vertex strip craniectomy procedures, with cephalic indices within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Shah et al concluded that endoscope-assisted strip craniectomy offers an effective treatment for sagittal craniosynostosis that is comparable for calvarial vault reconstruction, with no increase in morbidity. 24 The patients treated with endoscopic technique (n = 47) had significantly shorter hospital stay, less blood loss, lower transfusion rates, shorter operating times, and equivalent postoperative CIs (endoscopic 75.9, open 76.9) compared with patients who underwent open surgery (n = 42). The patients in the endoscopic group had been followed for 13 months, while those in the open group were followed for 24.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent surgical advances 13 have led to improvements in and thus a focus on minimally invasive therapeutic strategies 5 in infants affected with various forms of craniosynostosis. 19,24 First pioneered by Jimenez and Bar-A comparison of costs associated with endoscope-assisted craniectomy versus open cranial vault repair for infants with sagittal synostosis one, 12 endoscope-assisted craniectomy (EAC) performed in the first 6 months of life 11 has helped to decrease operative time, 26 blood loss, 18 transfusion requirements, 9 and hospital stays.…”
mentioning
confidence: 99%